X-Ray Scattering of Soft Matter - Stribeck, Norbert (Springer Laboratory, Manuals in Polymer Science,, 2007)
Applications of X-ray scattering to soft matter have advanced considerably within recent years, both conceptually and technically - mature high-power X-ray sources, synchrotrons and rotating anodes, as well as high-speed detectors have become readily available. High-quality time-resolved experiments on polymer structure now can be performed with ease, a major advancement due to the genuine power of the scattering method. This manual summarizes the analytical power of modern X-ray scattering in the field of soft matter. Description of simple tools that can elucidate the mechanisms of structure evolution in the studied materials is followed by a step-by-step guide and breakdown of the more advanced methods. Data analysis based on clear, unequivocal results is rendered simple and straightforward - with a stress on the carefully planning of the experiments and adequate recording of all required data. To this end, this book serves as a useful ready-reference guide.